IPO activity and market volatility. Issue 1 (12th March 2018) - Dicle, Mehmet F.; Levendis, John
Abstract : Purpose: The purpose of this paper is to hypothesize two channels in which market volatility affects initial public offering (IPO) activity. Design/methodology/approach: First, CEOs time the market for IPOs and volatility makes this decision process harder. Second, risk-averse IPO investors become more reluctant toward IPOs during periods of higher volatility for their after-IPO returns. Findings: The authors provide evidence that higher market volatility leads to lower IPO activity, supporting these hypotheses. More importantly, the authors show that it is not the realized volatility, but rather the implied (expected) volatility, that causes lower IPO activity. Research limitations/implications: While there may be many companies that are ready to have IPOs, they may be simply waiting for a more opportune time which may not necessarily be a period of high prices but of low volatility. Practical implications: The public policy prescription is clear: if IPOs are to be encouraged, then regulatory policies should be constructed with the aim of reducing volatility. Originality/value: This study is the first (to the authors' knowledge) to argue that it is not the realized volatility which most affects the IPO decisions of executives, entrepreneurs and investors.